2006
DOI: 10.1523/jneurosci.5297-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical Network ActivityIn VivoIs Generated through a Dynamic Balance of Excitation and Inhibition

Abstract: The recurrent excitatory and inhibitory connections between and within layers of the cerebral cortex are fundamental to the operation of local cortical circuits. Models of cortical function often assume that recurrent excitation and inhibition are balanced, and we recently demonstrated that spontaneous network activity in vitro contains a precise balance of excitation and inhibition; however, the existence of a balance between excitation and inhibition in the intact and spontaneously active cerebral cortex has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

69
781
6
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 923 publications
(859 citation statements)
references
References 63 publications
(90 reference statements)
69
781
6
3
Order By: Relevance
“…Given that these strong connections are clustered, and the highly nonrandom nature of synaptic connectivity, it is conceivable that pyramidal neurons with strong connections may be the recipient of suprathreshold AAC excitation. This provides an ideal mechanism for the rapid activation of large numbers of pyramidal neurons, as occurs in the transition from a hyperpolarized network Down state to the depolarized Up state (Steriade et al, 1993;Cossart et al, 2003;Haider et al, 2006), a phenomenon that has been observed not only in the cortex but also in the amygdala (Collins et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Given that these strong connections are clustered, and the highly nonrandom nature of synaptic connectivity, it is conceivable that pyramidal neurons with strong connections may be the recipient of suprathreshold AAC excitation. This provides an ideal mechanism for the rapid activation of large numbers of pyramidal neurons, as occurs in the transition from a hyperpolarized network Down state to the depolarized Up state (Steriade et al, 1993;Cossart et al, 2003;Haider et al, 2006), a phenomenon that has been observed not only in the cortex but also in the amygdala (Collins et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Alternating up states and down states can be readily observed in cerebral cortex during natural sleep or anaesthesia 30 , but they can be also induced in vitro by manipulating the ionic concentrations in a preparation so that they match those found in situ. Research showed that the up state is characterized by persisting synaptically mediated depolarization of the cell membranes owing to strong barrages of synaptic potentials, and a concomitant increase in spiking rate, whereas the down state is marked by membrane hyperpolarization and reduction or cessation of firing 31,32 . Most importantly, the excitation-inhibition conductances indeed changed proportionally throughout the duration of the up state despite large changes in membrane conductance 31,32 .…”
Section: What Do Activation Maps Represent?mentioning
confidence: 99%
“…Because the majority of interneurons synthesize and release γ-amino-butyric acid (GABA), they are also referred to as GABAergic or inhibitory interneurons [1] . The balance between excitation and inhibition is crucial, and the maintenance of dynamic equilibrium involves many physiological mechanisms [3] .…”
Section: Introductionmentioning
confidence: 99%